THE INFLUENCE OF LOCATION AND SERVICE QUALITY THROUGH GOOGLE REVIEWS ON PURCHASING DECISIONS (OMBAK LAUT ANCOL RESTAURANT) - Siti Zulaeha; Viniyati Maftuchach; Lela Nurlelawati (Asosiasi Dosen Muda Indonesia, 2025)
Analyzing the influence of location and service quality via Google Reviews on purchasing decisions at Ombak Laut Restaurant, Ancol, North Jakarta. In today's digital era, online reviews, especially via Google Reviews, have become an important factor influencing consumer perceptions and purchasing decisions. This research uses a quantitative approach with primary data collected through questionnaires distributed to 247 respondents, who are visitors to the Ombak Laut Restaurant. The independent variables in this research are location and service quality, the intervening variable is Google Reviews, and the dependent variable is purchasing decisions. The research method used is multiple linear regression to analyze direct and indirect relationships between variables. The research results show that location and service quality have a significant influence on Google Reviews. Furthermore, Google Reviews acts as a mediator that strengthens the influence of location and service quality on purchasing decisions. These findings show that strategic location, quality service, and positive reviews from consumers are an effective combination to encourage increased purchasing decisions. This research provides a practical contribution for Ombak Laut Restaurant managers in designing marketing strategies that focus on improving service quality and managing digital reviews to maintain competitiveness. Apart from that, the results of this research can also be a reference for similar research in the field of digital marketing management and the culinary industry. The limitation of this research lies in the sample coverage which only includes visitors to the Ombak Laut Restaurant in Dki Jakarta, so the results may not necessarily apply to other locations or types of businesses. Future research is expected to expand the object of study and consider additional factors, such as digital promotion and competition, to provide a deeper understanding of the influence of digital reviews.